HPV Prevalence and Genotype Distribution Among Women From Hengyang District of Hunan Province, China - Tang, Shuang-yang; Liao, Ya-qi; Hu, Yu; Shen, Hai-yan; Wan, Yan-ping; Wu, Yi-mou (Frontiers in Public Health, 2021)
Most cervical cancers were closely associated with human papillomavirus (HPV) infections. Therefore, understanding the ecological diversity of HPV prevalence and genotype distribution among various populations in different geographical regions was essential for optimizing HPV vaccination and maximizing the vaccination effects. A total of 12,053 patient data from the three-level hospitals in Hengyang city were retrospectively analyzed. In this study, the HPV prevalence was 10.16% overall, and the multiple-type infection rate was 1.83%. The HR-HPV infection rate was 8.52%. The top six HPV genotypes were as follows in descending order: HPV16, HPV58, HPV52, HPV39, HPV51, and HPV53. The HPV prevalence in the group above 60 years old was the most, and their HR-HPV infection rate corresponded to the most too. The infection rates of HPV and HR-HPV among outpatients were both lower than those among the hospitalized-patients, respectively. Among the hospitalized-patients, the infection rates of HPV and HR-HPV among the 50–60 years group were the most in both. The HR-HPV ratio-in-positive among HPV-positive patients with the histopathologic examination was higher than that among those patients without. Among 52 HPV-positive patients with cervical squamous carcinoma, the ratio-in-positive of HPV16 was 61.54%. This study demonstrated that the HPV prevalence varied with age among women from Hengyang district of Hunan province in China and showed that HPV16, HPV58, HPV52, HPV39, HPV51, and HPV53 genotypes were more popularly distributed in this region, which could provide the experimental basis for Chinese public health measures on cervical cancer prevention.